Business Actors Liability For Defective Products In The Perspective Of Law Number 8 Of 1999 Concerning Consumer Protection - Noviyani, Nia; Sigit Wibowo (Fakultas Hukum Universitas Widya Mataram, 2026)
This research originates from the issue of increasing consumer losses caused by detective, damaged, or misleading products that do not correspond to the information promised by business actors. The purpose of this study is to analyze and identify the forms of business actors’ responsibility for detective products as reviewed under Law Number 8 of 1999 concerning Consumer Protection, as well as the regulation of cinsumers rights to obtain compensation under the same law. The research method used is normative juridical with a statutory approach and literature study of primary and secondary legal sources. The results show that business actors have strict liability for losses suffered by consumer do to defective products. The forms of compensation may includerefunds, products replacements, medical care, or financial assistance, which must be provided within seven (7) days after the transaction. Consumers rights to obtain compensation are regulated in Articles 4, 19, and 23 of Law Number 8 of 1999 concerning Consumer Protection. In the event of a dispute, resolution can be carried out trhough non-litigation (Consumer Dispute Settlement Agency) or litigation (court)